POLITIK RECALLING DALAM PARLEMENT RIAU 2014 - 2019 - Yandra, Alexsander (Universitas Riau, 2016)
The Interim Replacement between the time (PAW) mechanism of six legislators of Riau at 2014-2016 periodthrough the long mechanism and give rise to polemics both at the elite level and on the society. Strating from theproposal for dismissal by the regional council (DPD) of political parties, approval at the meeting of DPRD,verification of the KPUD of Riau Provinces, the letter proposal that then forwarded to the Minister for issuedofficial announcement of PAW. Delays in the Minister?s decree related determination replacement PAW of the sixlegislators Riau who participate in 2015 election implication for the vacancy delegation in constituency of thesix legislators who resigned. This is administratively highly influential DPRD of Riau in decision making and forthe local elections also will impact to reduced their delegations in government. This research used the turnoverbetween the time (PAW) concept and theory of political delegation institutions. This research type is descriptivewith qualitative approach, the data collection technique used depth interviews and documentations.The results showed that the mechanism of the six legislators Riau PAW 2014-2019 period after the enactmentinto regional head candidates in the elections of December 2015 the dynamics of the level of Parliament andpolitical parties Bearers and take quite long. That condition has implications for vacancies in representativeinstitutions (parliament) Riau province where administratively is not full members of Parliament in decisionmakingso that the delay in setting the budget Riau in 2016.